Linking Danube River activity to Alpine Ice-Sheet fluctuations during the last glacial (ca. 33–17 ka BP): Insights into the continental signature of Heinrich Stadials. (1st February 2020) - Martinez-Lamas, Ruth; Toucanne, Samuel; Debret, Maxime; Riboulot, Vincent; Deloffre, Julien; Boissier, Audrey; Cheron, Sandrine; Pitel, Mathilde; Bayon, Germain; Giosan, Liviu; Soulet, Guillaume
Abstract: Offshore archives retrieved from marine/lacustrine environments receiving sediment from large river systems are valuable Quaternary continental records. In the present study, we reconstruct the Danube River activity at the end of the last glacial period based on sedimentological, mineralogical and geochemical analyses performed on long-piston cores from the north-west Black Sea margin. Our data suggest that the Danube River produced hyperpycnal floods throughout the ca. 33–17 ka period. Four main periods of enhanced Danube flood frequency, each of 1.5–3 kyr duration, are recorded at ca. 32.5–30.5 ka (equivalent to the first part of Heinrich Stadial –HS– 3), at ca. 29–27.5 ka (equivalent to Greenland Stadial 4), at ca. 25.3–23.8 ka (equivalent to HS 2) and at ca. 22.3–19 ka. Based on mineralogical and geochemical data, we relate these events to enhanced surface melting of the Alpine Ice Sheet (AIS) that covered ∼50, 000 km 2 of the Danube watershed at the Last Glacial Maximum (LGM). Our results suggest that ( i ) the AIS growth from the inner Alps to its LGM position in the northern Alpine foreland started from ca. 30.5 ka, ended no later than ca. 25.3 ka, and was interrupted by a melting episode ca. 29–27.5 ka; ( ii ) the AIS volume drastically decreased from ca. 22.3 to 19 ka, as soon as summer insolation energy at the AIS latitude increased; and ( iii ) HSs strongly impacted the AIS mass balance through enhanced summer surface melt. This, together with evidence of severely cool winters and the rapid expansion of sea ice in the North Atlantic, implies strong seasonality in continental Europe during stadials. Highlights: High-resolution record of the Danube River floods over the ca. 33–17 ka period. Flood frequency likely related to mass-balance changes of the Alpine Ice Sheet (AIS). Increasing surface melt of the AIS during Heinrich Stadials and the early deglaciation. Warm western European summers likely prevailed during Heinrich Stadials.